A two-dimensional dynamic finger modeling for the analysis of repetitive finger flexion and extension - Yun, Myung Hwan; Jun Eoh, Hong; Cho, Janghyeon (International journal of industrial ergonomics, 2002)
Analysis of finger motion is an important aspect of hand motion analysis. Studies on finger motion have been relatively few due to the lack of suitable measurement devices. With the advances of sensor technology, devices such as CyberGlove TM now have the capability of measuring finger articulation angles in real time. The objective of this study was to analyze repetitive finger flexion and extension with the measurement data from the CyberGlove TM system. To investigate the dynamic characteristics of the finger movement, the dynamic equations of motion from robot arm dynamics was adopted and modified. Hand anthropometric data such as the mass of finger segment, length of finger segment, and thickness of joint were measured for eight male subjects. CyberGlove TM was used to measure joint angles of each finger during repetitive flexion and extension. Two kinds of flexion and extension motion were studied. A bare-hand finger flexion and extension wearing the CyberGlove TM was studied first. A keyboard-typing task was studied as the simulation of the real task. Results from the two experiments with repetitive finger flexion and extension showed that the dynamic characteristics of the finger motion should be included in the consideration of the loads on the hand during manual task. The result also showed that, unlike the assumptions employed by many studies, finger motion is significantly different between different fingers and joints. When compared with the simulation result from literature, our result showed that the proximal interphalangeal and distal interphalangeal movement for the index finger corresponded well with the simulation results while other joints did not. This study also showed that the dynamic equations of motion can be used to calculate angular moments of the finger joints. Most of the workers are still using manual tools to carry out tasks. In order to design and evaluate manual tasks and tools, dynamic modeling of hand motion is of importance. This study deals with 2-D dynamic model for finger motion that is an important aspect of hand motion analysis.